2007
DOI: 10.1002/cnm.1040
|View full text |Cite
|
Sign up to set email alerts
|

An approach to coupled thermal hydraulics and structural mechanics problems for the MEGAPIE spallation source target

Abstract: SUMMARYThis paper describes some novel heat transfer and stress analysis problems that arose in the context of demonstrating the cooling principle of a liquid-metal neutron spallation source target. The design studies using computational fluid dynamics (CFD) resulted in an optimum flow configuration being defined for the coolant circulation. Simultaneously, stresses in the structural components were examined using finite element method (FEM) techniques. Central to the coupled CFD/FEM analysis strategy was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…Analysis of the accident sequence requires the coupled application of a CFD tool-in our case CFX-4 12) -and a structural analysis code-in this case ABAQUS 16) -with transient data being interfaced between them. 4) The lower target schematic given in Fig. 15(a) illustrates the accident sequence.…”
Section: Transient Analysis Of the Target Hull Under Thermal Shockmentioning
confidence: 99%
“…Analysis of the accident sequence requires the coupled application of a CFD tool-in our case CFX-4 12) -and a structural analysis code-in this case ABAQUS 16) -with transient data being interfaced between them. 4) The lower target schematic given in Fig. 15(a) illustrates the accident sequence.…”
Section: Transient Analysis Of the Target Hull Under Thermal Shockmentioning
confidence: 99%
“…The temperature contours clearly reflect the elliptical form of the beam footprint. Again, the associated stress analysis 4) revealed that, despite the strong temperature gradient in the centre of the window, the high stress concentrations actually occur in the outer section, near the flow guide attachment points, where the material is thicker and curvatures are high. The calculation also revealed that the internal D 2 O pressure (corresponding to a 6 bar overpressure) has a nontrivial effect on the stress distribution.…”
Section: Steady-state Analysis Of the Safety Hull In Normal Operationmentioning
confidence: 99%
“…A Computational Fluid Dynamic Studies of the MEGAPIE Spallation Source Target and Safety Vessel transient, conjugate heat transfer calculation was performed, starting from a normal operating mode, with the beam at full power. Data files 4) containing the information needed to compute the stresses were written at specified time intervals during the run (50 ms over most of the transient, but 5 ms around the time of maximum stress). This procedure also allowed checking of the time-step dependence of the results.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation